Family Interventions for Schizophrenia and the Psychoses: A Review. Issue 3 (14th July 2016) - McFarlane, William R.
Abstract : Family psychoeducation as a treatment for schizophrenia was developed 40 years ago almost simultaneously and independently by investigators who at the time were not family therapists. Although the original goal was to decrease high expressed emotion as a means of preventing relapse, later variations have gone beyond to focus on social and role functioning and family well‐being. Explicitly disavowing the earlier assumptions that family pathology caused relapse and deterioration, family psychoeducation seeks to engage family members as more sophisticated partners, complementing interventions by clinicians with specialized interactions and coping skills that counter the neurologic deficits inherent to the disorder. It has proved to be one of the most consistently effective treatments available. Reports on outcome studies now number more than 100, while meta‐analyses put relapse rate reduction at 50–60% over treatment as usual. The most recent application in first episode and prodromal psychosis, combined with other evidence‐based interventions, is yielding perhaps the most promising results yet achieved—substantial return of functioning and avoidance of psychosis altogether. Reviewed here are its scientific, theoretical, and clinical sources, a description of the most commonly applied version—the multifamily group format, selected clinical trials spanning those four decades, international and ethnic adaptations, and studies on mechanisms of efficacy. Abstract : Translation into Chinese